The Potential Role of Vitamin D in the Development of Tuberculosis in Chinese Han Population: One Case-Control Study - Cai, Li; Hou, Shuangyi; Huang, Yadong; Liu, Shuang; Huang, Xibao; Yin, Xiaoxv; Jiang, Nan; Tong, Yeqing (Frontiers in Medicine, 2022)
Background/Aims: Spinal Serum 25-hydroxyvitamin D (25[OH]D) status plays an important role in mediating innate immune responses by acting as a cofactor for induction of antimycobacterial activity and is thus involved in the development of Tuberclosis (TB). Results reported regarding the association of vitamin D with TB remained controversial. We aimed to identify any common association between 25[OH]D status and TB in Chinese Han population. Methods: 280 subjects (70 TB patient and 210 age-and-sex matched controls) were recruited. TB cases were diagnosed based on the presence of acid-fast bacilli on smears from sputum, and MTB isolation. Healthy controls were randomly selected from two local community-based populations. 25[OH]D was detected by electrochemiluminescence immunoassay (ECLIA) on Roche Elecsys before the initial treatment. Multivariate logistic regression analysis was used to examine the association of Vitamin D with TB. Results: There was no significant difference on the serum vitamin D level between total cases and controls, but we found a strong tendency toward a higher level of serum vitamin D in male population (P < 0.05) with TB but not in female. High serum vitamin D increased the risk of TB in Chinese Han population (OR=1.035, 95%CI: 1.001-1.070, P < 0.05). The serum vitamin D level was significantly decreased with age increasing in cases and controls (all P < 0.001). Conclusions: High serum vitamin D maybe an independent risk factor for TB in Chinese Han population.